Fornical and nonfornical projections from the rat hippocampal formation to the anterior thalamic nuclei. Issue 9 (3rd March 2015) - Dillingham, Christopher M.; Erichsen, Jonathan T.; O'Mara, Shane M.; Aggleton, John P.; Vann, Seralynne D.
ABSTRACT The hippocampal formation and anterior thalamic nuclei form part of an interconnected network thought to support memory. A central pathway in this mnemonic network comprises the direct projections from the hippocampal formation to the anterior thalamic nuclei, projections that, in the primate brain, originate in the subicular cortices to reach the anterior thalamic nuclei by way of the fornix. In the rat brain, additional pathways involving the internal capsule have been described, linking the dorsal subiculum to the anteromedial thalamic nucleus, as well as the postsubiculum to the anterodorsal thalamic nucleus. Confirming such pathways is essential in order to appreciate how information is transferred from the hippocampal formation to the anterior thalamus and how it may be disrupted by fornix pathology. Accordingly, in the present study, pathway tracers were injected into the anterior thalamic nuclei and the dorsal subiculum of rats with fornix lesions. Contrary to previous descriptions, projections from the subiculum to the anteromedial thalamic nucleus overwhelmingly relied on the fornix. Dorsal subiculum projections to the majority of the anteroventral nucleus also predominantly relied on the fornix, although postsubicular inputs to the lateral dorsal part of the anteroventral nucleus, as well as to the anterodorsal and laterodorsal thalamic nuclei, largely involved a nonfornical pathway, via the internal capsule. © 2015 The Authors Hippocampus Published by Wiley Periodicals, Inc.